Anti-inflammatory activity of roots of Achyranthes aspera - S., Vijaya Kumar; P., Sankar; R., Varatharajan (Taylor & Francis, 2009)
This study investigated the anti-inflammatory potential of the alcohol extract of Achyranthes aspera Linn. (Amaranthaceae) in Wistar rats after oral administration (50, 100, and 200 mg/kg). This was done using the carrageenan-induced paw edema method (acute inflammatory model) and cotton pellet granuloma test (chronic inflammatory model). The alcohol extract showed significant suppressed granuloma formation. Collectively, these data demonstrate promising anti-inflammatory activity against both acute and chronic inflammation. In addition, inhibition of prostaglandins and bradykinins may play a role. This study reveal- ing the promising anti-inflammatory activity of Achyranthes aspera roots has been carried out scientifically for the first time.